Well Water Quality of Residents in The Tofu Industry, Pakintelan Village, Gunungpati District - Hanifa Putri Sajida; Andhina Putri Heriyanti; Rifa'atunnisa Rifa'atunnisa; Amnan Haris; Putri Alifa Kholil; Abdul Jabbar; Trida Ridho Fariz (Yayasan Keluarga Guru Mandiri, 2026)
Small and medium-sized industries, particularly the tofu industry, are often characterized by low energy efficiency and high pollution due to a lack of industrial wastewater treatment, leading to direct discharge that degrades water bodies and the surrounding well water quality. This study aims to analyze the quality of well water near the tofu industry in Pakintelan Village, Gunungpati District, Semarang City, to assess its suitability as drinking water. A quantitative descriptive research approach was used with purposive sampling. Data were collected through observation, interviews, and laboratory tests focusing on physical (Odor, Taste, TDS), chemical (pH, Nitrate, Nitrite), and biological (Coliform) parameters from residents' wells. The quality status was determined using the STORET Index method and an ANOVA test, in accordance with the Minister of Health Regulation No. 02 of 2023. The results confirmed that tofu liquid wastewater negatively affects well water quality, and that the distance between the well and the tofu industry significantly influences this water quality. This research contributes to environmental science by providing empirical evidence of the direct contamination pathway from untreated tofu effluent to domestic water sources and highlighting well distance as a critical factor in managing water resources in industrial areas.